2021
DOI: 10.3389/fmicb.2021.633428
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Insight Into Patterns and Mechanism of Nitrogen Cycle During Biocrust Succession

Abstract: The successional ecology of nitrogen cycling in biocrusts and the linkages to ecosystem processes remains unclear. To explore this, four successional stages of natural biocrust with five batches of repeated sampling and three developmental stages of simulated biocrust were studied using relative and absolute quantified multi-omics methods. A consistent pattern across all biocrust was found where ammonium assimilation, mineralization, dissimilatory nitrite to ammonium (DNiRA), and assimilatory nitrate to ammoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 108 publications
2
8
0
Order By: Relevance
“…Approximately half of arid and semiarid drylands are devoid of plants and are instead occupied by biological soil crusts (BSCs), an assemblage of soil fine particles, cyanobacteria, green algae, lichen, mosses and microbes in various proportions ( Belnap, 2001 ). BSCs support a wide range of ecosystem functions, such as enhancing soil stability, reducing soil and wind erosion, improving the nutrient cycling of ecosystems, regulating water availability and redistribution, and influencing the emergence and survival of vascular plants ( Belnap and Lange, 2003 ; Maestre et al, 2011 ; Wang et al, 2021 ; Barrera et al, 2022 ). Given the global distribution of BSCs and their key functional roles in the ecosystems where they are prevalent, understanding the developmental mechanisms and ecological functions of BSCs is critical in formulating sustainable natural resource management and conservation policies in drylands.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately half of arid and semiarid drylands are devoid of plants and are instead occupied by biological soil crusts (BSCs), an assemblage of soil fine particles, cyanobacteria, green algae, lichen, mosses and microbes in various proportions ( Belnap, 2001 ). BSCs support a wide range of ecosystem functions, such as enhancing soil stability, reducing soil and wind erosion, improving the nutrient cycling of ecosystems, regulating water availability and redistribution, and influencing the emergence and survival of vascular plants ( Belnap and Lange, 2003 ; Maestre et al, 2011 ; Wang et al, 2021 ; Barrera et al, 2022 ). Given the global distribution of BSCs and their key functional roles in the ecosystems where they are prevalent, understanding the developmental mechanisms and ecological functions of BSCs is critical in formulating sustainable natural resource management and conservation policies in drylands.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, some bacterial phyla, such as Bacteroides and Cyanobacteria, can secrete metabolites or form centimeter-long filament bundles to maintain the physical structure of BSCs ( Garcia-Pichel and Wojciechowski, 2009 ). Moreover, as primary producers, bacteria (primarily cyanobacteria) increase soil fertility by fixing carbon and nitrogen in the atmosphere, providing a strong foundation for the development of BSCs ( Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dominant community in parts A and B are γ-Proteobacteria, accounting for 23%, while the dominant microbe in part C is α-Proteobacteria (33%). γ-Proteobacteria can be involved in the degradation of nitrate and other contaminants in bioreactors [ 18 , 19 ], and α-Proteobacteria also play an important role in the denitrification reaction [ 20 ]. Moreover, the three micro-organisms with the highest proportion in D, E, F and G are γ-proteobacteria (15–25%), β-Proteobacteria (10–15%) and α-Proteobacteria (17–22%).…”
Section: Resultsmentioning
confidence: 99%
“…The second and third dominant classes were Beta- and Gammaproteobacteria with an operation time of 30 days, while the order was reversed with an operation time of 60 days. A relevant study pointed out that Alpha - and Betaproteobacteria are potential nitrogen fixers, that Alphaproteobacteria plays an important role in each step of denitrification, and that Betaproteobacteria is very important for ammonia oxidation [ 25 ]. However, previous studies had reported the presence of Gammaproteobacteria as the predominant microorganism in MBfRs used to reduce nitrates and other contaminants [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%